A review on battery technology for space application. (May 2023) - Pathak, Anil D.; Saha, Shalakha; Bharti, Vikram Kishore; Gaikwad, Mayur M.; Sharma, Chandra Shekhar
Abstract: This review article comprehensively discusses the energy requirements and currently used energy storage systems for various space applications. We have explained the development of different battery technologies used in space missions, from conventional batteries (AgZn, NiCd, NiH2 ), to lithium-ion batteries and beyond. Further, this article provides a detailed overview of the current development of lithium batteries concerning their different electrode and electrolyte system, which needs special consideration for enabling their use for space application. This review also provides an outlook on the battery technology development for interplanetary space missions enlisting the research emphasis to be directed to meet the special energy requirements during various stages of such missions. This review is an attempt to provide a one-step comprehensive overview for any researchers, scientists, batteries manufacturers, and space agencies to first understand the current requirements critically and, accordingly, the solutions to prepare a future roadmap to develop highly efficient, next-generation advanced energy storage systems to mitigate the technical challenges and at the same time, minimizing the cost associated. Graphical abstract: Unlabelled Image Highlights: Requirement of battery system for space application Primary, secondary, and nuclear batteries for space application Battery for planetary system, spacecraft, and extravehicular activity Beyond Li-ion battery including LiS, Li-CO2, and the nuclear battery for space application